Knowledge and willingness towards malaria vaccines among caregivers in Dar es Salaam, Tanzania - Felista Mwingira; Deokary Matiya; Frank Chacky (Malaria Journal)
Abstract Background Tanzania is a malaria-endemic country that relies solely on anti-malarial drugs and vector control measures, including insecticide-treated bed nets and indoor residual spraying. However, the growing resistance to these interventions threatens their effectiveness, highlighting the need for additional strategies to accelerate malaria eradication efforts. Currently, malaria vaccines have begun to roll out in endemic areas. However, hesitancy emanating from misinformation on vaccine efficacy and safety has been recorded in various parts of the world. In this context, this study investigated the knowledge and willingness of caregivers towards the malaria vaccine. Methods This is a health facility-based cross-sectional survey conducted from September 2022 to March 2023. In total, 293 caregivers attending Ante-Natal Clinics (ANC) in selected health facilities in Dar es Salaam were recruited. A semi-structured questionnaire was used to collect caregivers’ demographic information, knowledge of malaria, knowledge of malaria vaccines and willingness to receive malaria vaccines. Results The respondents were predominantly women (97.3%) aged 18 to 52 years. Overall, 87.4% had knowledge of malaria disease, while 14% did not know how malaria is transmitted. Most respondents (86.3%) knew about malaria prevention/control methods. However, only 14.7% of the recruited caregivers were aware of the malaria vaccine. Of those exposed to vaccine messages, 67.4% were aware that the vaccine was for children under 5 years of age, while 53.5% knew that the vaccine was for pregnant women. Despite their low exposure, most respondents (92.8%) were willing to receive the malaria vaccine for their children under five years. Conclusion Malaria knowledge and willingness to vaccinate against malaria was high among Tanzanian caregivers despite the low awareness of malaria vaccines. This suggests the need for targeted information, education and communication strategies (IECs) for communities to curb misconceptions and complement their high willingness to accept the malaria vaccine in Tanzania.